DIGITAL MEDIA LITERACY IN JORDAN: CHALLENGES AND DEVELOPMENT - Mohamad Ahmad Abdallah Abu Halka; Shafizan Mohamed (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Digital media literacy refers to having the ability to use digital technologies to participate in and contribute to social, cultural, political, and economic life. It includes understanding the impact of recent technologies on society, understanding and having the ability to manage digital identities fittingly, and having the ability to find, organize, understand, evaluate, analyze and create digital information. While the level of digital media literacy in Jordan is still in its infancy, there is a positive move towards educating the Jordanian people about digital media. Recently the Jordanian government has developed a national executive plan for digital media literacy to develop community awareness and improve its capabilities in dealing with information and media sources during the Corona pandemic through the Ministry of Culture, Therefore, in this study, we will review the digital media literacy in Jordan and we will study the challenges and development of digital media literacy in Jordan.